Kontribusi Explosive Power Otot Lengan Dan Koordinasi Mata Tangan Terhadap Kemampuan Servis Atas Pada Siswa Putra Ekstrakurikuler Bolavoli Di MTS Muhammadiyah 02 Pekanbaru - ., Adinda Aulia Firna Dewi; ., Zulrafli (CV. ITTC INDONESIA, 2023)
The purpose of this study was to determine the contribution of explosive power of the arm muscles and eye hand coordination to the upper service ability of 18 male extracurricular volleyball students at MTS Muhammadiyah 02 Pekanbaru. This type of research is correlational research. The sampling technique in this research is purposive sampling, which is a sampling technique with certain considerations. male students in the volleyball extracurricular can be directed and can serve the volleyball.The research instrument used was a test to measure the explosive power of the arm muscles, namely the two hand medicine ball put test, the test to measure eye hand coordination was the throwing and catching test of a tennis ball, and the volleyball service skill test. The data analysis technique used is the Pearson product moment correlation technique and multiple correlation. The conclusions in this study are: 1) there is a contribution of explosive power of the arm muscles (X1) to the upper service ability of male students in the volleyball extracurricular activity at MTS Muhammadiyah 02 Pekanbaru with a correlation coefficient percentage of 38.68% , 2) there is a contribution of eye hand coordination (X2) to the upper service ability of male extracurricular volleyball students at MTS Muhammadiyah 02 Pekanbaru with a correlation coefficient percentage of 25.2%, 3) there is an explosive power contribution arm muscle and eye hand coordination (X1 X2) on upper service ability (Y) in male volleyball extracurricular students at MTS Muhammadiyah 02 Pekanbaru with a correlation coefficient percentage of 41.9%.